The Political Opinions of Swedish Social Scientists - Niclas Berggren; Henrik Jordahl; Charlotta Stern (Research Institute of Industrial Economics (IFN), 2007)
We study the political opinions of Swedish social scientists in seven disciplines. A survey was sent to 4,301 academics at 25 colleges and universities, which makes the coverage of the disciplines included more or less comprehensive. When it comes to party sympathies there are 1.3 academics on the right for each academic on the left a sharp contrast to the situation in the United States, where Democrats greatly dominate the social sciences. The corresponding ratio for Swedish citizens in general is 1.1. The most left-leaning disciplines are sociology and gender studies, the most right-leaning ones are business administration, economics, and law, with political science and economic history somewhere in between. The differences between the disciplines are smaller in Sweden than in the more polarized U.S. We also asked 14 policy questions. The replies largely confirm the pattern of a left-right divide but overall the desire to change the status quo is tepid.
Keywords: A11; A13; A14; 330; Academics; Social Scientists; Policy Views; Political Opinions; Party Sympathies; Sozialwissenschaftler; Meinung; Weltanschauung; Politische Partei; Schweden